SENSORY CHARACTERISTICS PRODUCTS OF CASSAVA COOKIES FORTIFIED WITH FERRO SULFAT FOR PREVENTION ANEMIA - Auliana, Rizqie (Home Economics Journal, 2022)
The research aims to: Find the recipe cookies cassava flour fortified iron (ferrous sulfate), Determine the sensory characteristics of cookies cassava flour fortified iron (ferrous sulfate) and Know the acceptance of cookies cassava flour fortified iron ( ferrous sulfate).  This type of research is experimental. The research phase consists of preliminary research to find a recipe cookies reference, primary research first to find cookies recipe chosen and the 2 major research to find a recipe cookies cassava flour with iron fortification ferro sulfate (iron cookies). Furthermore, the study continued to determine the sensory characteristics of cookies iron using Free Choice Profiling (FCP) and Focus Groups Discussion (FGD) as well as the acceptance test using a hedonic test. Results of the study: finding the right recipe to make a reference to cookies iron is Syringes Cookies using cassava flour to replace 100% of wheat flour. The amount of iron added to 500 mg per 1 prescription for a total of 700 g flour. Results so the product is 14 packs containing 10 pieces of cookies weighing ± 90 g to 1 servings. Characteristics cookies cassava flour fortified iron ferrous sulfate in overalls (appearance overall) is attractive with rounded forms and decorated with glazing and sprinkled sprinkle with color cookies yellow, has had the aroma of cookies are actually having been flavored butter, as well as the sweetness enough offset savory butter beremah but too soft texture that is less crisp. Test results received power over these cookies iron showed that more than 50% of panelists liked the cookies cassava flour with ferrous sulfate iron fortification of the attributes of overall appearance (overall), color, texture and flavor. While the aroma attributes can be concluded not preferred because only 42.86% of panelists who love the smell of cookies iron. However the overall cookies iron is preferred so that it can be recommended as a food supplement for the prevention of anemia in adolescent girls and the research hypothesis can be accepted, namely the addition of iron ferrous sulfate does not damage the overalls, color, aroma, taste and texture of cookies so that the final outcome cookies flour iron-fortified cassava ferrous sulfate can be accepted or preferred by the panelists. Cookies iron can be recommended as an alternative supplementary food for the prevention of anemia in adolescent girls.